Analisis Multi Slice Computed Tomography (MSCT) Nasofaring Dengan Klinis Karsinoma Nasofaring Di Instalasi Radiodiagnostik RSUP Dr. Hasan Sadikin Bandung - Destri Bestari Palimbong; Anak Agung Aris Diartama; I Kadek Sukadana (Jurnal Pengabdian Ilmu Kesehatan, 2023)
Background: Nasopharyngeal carcinoma is cancer that occurs in the nasopharyngeal mucosa which shows squamous cell differentiation. MSCT has become a reliable imaging technique for assessing the extent of nasopharyngeal carcinoma. Nasopharyngeal MSCT examination procedure with clinical nasopharyngeal carcinoma at the Radiodiagnostic Installation of Dr. RSUP. Hasan Sadikin Bandung uses a head protocol and slice thickness of 3-5 mm. This study aims to determine the Nasopharyngeal MSCT examination procedure for clinical nasopharyngeal carcinoma using a head protocol with manual intravenous contrast injection. Method: The type of research used is descriptive qualitative research with a case study approach. This research was conducted at the Radiodiagnostic Installation of RSUP Dr. Hasan Sadikin Bandung The subjects in this study consisted of three patients, two radiographers and three radiologists. Data collection methods are carried out through observation, interviews and documentation. The data analysis technique used is an interactive analysis model.